(x-1)(x+2)(x+3)(x+6)
=[(x-1)(x+6)][(x+2)(x+3)]
=(x^2+5x-6)(x^2+5x+6)
=(x^2+5x)^2-36>=-36
=>min=-36<=>x=0 hoặc x=-5
\(VìA=(x-1).(x+2).(x+3).(x+6)\)\(\Rightarrow\)\(A=x.(-1+2+3+6)\)\(\Rightarrow\)\(A=x.10\)
Vì A nhỏ nhất \(\Rightarrow\)A=0 mà A=x.10\(\Rightarrow\)0=x.10\(\Rightarrow\)x=0\(:\)10\(\Rightarrow\)x=0
\(Vậy\) \(A\) \(nhỏ\) \(nhất\) \(khi\) x=0
\(Vì\)\(A=\) \((x-1).(x+2).(x+3).(x+6)\)\(\Rightarrow\)\(A= \)\(x.(-1+2+3+6)\)\(\Rightarrow\)\(A=x.10\)
\(Vì\) \(A\) \(nhỏ\) \(nhất\)\(\Rightarrow\)\(A=\)0 \(mà\) \(A=x.10\) \(\Rightarrow\)\(x.10= 0\)\(\Rightarrow\)\(x=0:10\)\(\Rightarrow\)\(x=0\)
\(Vậy\) \(A \) \(nhỏ\) \(nhất\) \(khi\) \(x=0\)